Empirical analysis of airline choice using survey data in Hong Kong - MEI-LING TAM (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This research aims to determine how much various choice factors matter when selecting an airline. This research aims to determine which factors are most significant to Hong Kong air travellers when making plans.Method: The residents of Hong Kong are polled in an empirical study to collect the necessary information. The manager at a conventional travel agency and three frequent flyers were interviewed in depth. There were a total of 387 responses to the survey.Findings: The findings revealed substantial differences in service perceptions between passengers of different ages and income levels, those who travel for business versus leisure, and those who play a decision-making versus a supporting role during a trip. According to the data, price is the most important consideration for passengers when selecting an airline and booking a flight. Possibly because of this, Low-Cost Carriers (LCC) have been gaining market share in recent years. Full-Service Carriers (FSC) can compete better with LCCs if they prioritise efficient flight operations, increasing flight frequency and decreasing delays. Since passengers place a premium on these considerations.Implications/Novel Contribution: To our knowledge, this is the first empirical study to examine how customers decide which airline to fly with based on how they made their reservations.